DAMPAK BELANJA PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI DAERAH: STUDI KASUS DATA PANEL PROVINSI DI INDONESIA - Nur Widiastuti; Ary Sutrischastini (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to identify the effect of government spending and other fiscal variables on economic growth and per capita income in 33 provinces in Indonesia. Other fiscal variables used are personnel expenditures, capital expenditures and goods and services expenditures. The data used is panel data in 33 regions in Indonesia, data obtained from Kemenkeu.go.id. The source of provincial-level data is obtained from the APBD summary issued by the Directorate General of Budget, Ministry of Finance of the Republic of Indonesia. The estimation method is Pooled Least Squares. The estimation results show that the variables of Government Expenditure, Government Expenditure per Capita, and share of Government Expenditure on GRDP have no effect on economic growth but positively affect income per capita. Meanwhile, other fiscal variables consisting of personnel expenditure, capital expenditure and expenditure on goods and services, in the form of total, per capita and share of GRDP, have a positive effect on economic growth and income per capita. The recommendation from this research is for the provincial government to map its spending well so that the goal of increasing people's income can be achieved.